The development of smell therapy device for autism child / Nurul Huda Mohamd Saleh … [ et al.] - Ismail, Shafinar (Division of Research and Industry Linkages, 2017)
Autism is an abnormal developmental disability that comes from disorder of neurological which effect the brain function. While, Olfactory Dysfunction is considered a Sensory Processing Disorder involving an altered sensitivity to smells may and may cause by Autism Spectrum Disorder (ASD). in this project, we developed a smell therapy device to study the development of smell function on Autism children. This smell therapy device is developed to provide an interactive smell therapy device as a two-way communication between the user and the caretaker. Six (6) subjects was chosen in this study which vary from severe and mild autistic children and a normal child as a control. The validity of the study was tested for six (6) days where the subjects inhale the smell that spread out form the device and try to guess the scent. While for the reliability of the device are from the autism child caretaker by, answering the questionnaire after use the product at least once. The findings showed this device is successfully developed with positive feedback and it also succeed to improve the smell focusing sensitivity of the autism child.